Synopsis: Subnational variation in policy implementation: The case of Nigerian land governance reform - Resnick, Danielle; Okumo, Austen (International Food Policy Research Institute, 2017)
This study focuses on differential implementation of Systematic Land Tenure Regularization (SLTR) across Nigerian states in order to understand the set of conditions that are more likely to facilitate reform. Geographically, the study focuses on six states: Cross River, Jigawa, Kaduna, Kano, Katsina, and Ondo between 2012 and 2016. Methodologically, process-tracing was combined with a comparative analysis across the six states based on semi-structured interviews conducted with more than 90 stakeholders between July and October 2016.